Transmission Mechanism Of Twin Deficits Hypothesis: Evidence From Two Neighbouring Countries - Lau, Evan; Chan, Tze Haw (INTI University College, 2003)
In spite of the apparent importance of the effect of budget deficit on macroeconomic variables, not much empirical work has been carried on the ASEAN economies. Hence, the primary objective of this study is to establish the causal relationship between the twin deficit. An insight on the particular story of twin deficits nexus in Malaysia and Thailand is presented in this paper. The role of exchange rate and interest rate which acts as a source transmission mechanism are proven to be important in the innovation of twin deficits debate and a version of a ‘vicious circle’ is detected in Malaysia. First, we found causality run from budget deficit to current account deficit (Keynesian paradigm) for Thailand and bi-directional causality for Malaysia. Second, on the whole, budget deficit is the driving force for interest rate, exchange rate and current account where the transmission mechanism channel operates through exchange rate and interest rate between the two deficits, supporting a version of Abell’s causal chain (or Keynesian view). Third the exchange rate was found to “Granger” cause current account deficit and not vice versa.